PS1-11aop: Probing the Mass-loss History of a Luminous Interacting Supernova Prior to Its Final Eruption with Multiwavelength Observations - Adaeze L. Ibik; Maria R. Drout; Raffaella Margutti; David Matthews; V. Ashley Villar; Edo Berger; Ryan Chornock; Kate D. Alexander; Tarraneh Eftekhari; Tanmoy Laskar; Ragnhild Lunnan; Ryan J. Foley; et al. (The Astrophysical Journal)
Luminous interacting supernovae (SNe) are a class of stellar explosions whose progenitors underwent vigorous mass loss in the years prior to core collapse. While the mechanism by which this material is ejected is still debated, obtaining the full density profile of the circumstellar medium (CSM) could reveal more about this process. Here, we present an extensive multiwavelength study of PS1-11aop, a luminous and slowly declining Type IIn SNe discovered by the Pan-STARRS Medium Deep Survey. PS1-11aop had a peak r -band magnitude of −20.5 mag, a total radiated energy >8 × 10 ^50 erg, and it exploded near the center of a star-forming galaxy with super-solar metallicity. We obtained multiple detections at the location of PS1-11aop in the radio and X-ray bands between 4 and 10 yr post-explosion, and if due to the supernova (SN), it is one of the most luminous radio SNe identified to date. Taken together, the multiwavelength properties of PS1-11aop are consistent with a CSM density profile with multiple zones. The early optical emission is consistent with the SN blastwave interacting with a dense and confined CSM shell, which contains multiple solar masses of material that was likely ejected in the final <10–100 yr prior to the explosion, (∼0.05−1.0 M _⊙ yr ^−1 at radii of ≲10 ^16 cm). The radio observations, on the other hand, are consistent with a sparser environment (≲2 × 10 ^−3 M _⊙ yr ^−1 at radii of ∼0.5–1 × 10 ^17 cm)—thus probing the history of the progenitor star prior to its final mass-loss episode.